Facial Recognition Systems under the European Union's Artificial Intelligence Act - Villafuerte-Guerrero, Gabriela (2024)
The human eye can distinguish one person from another by identifying them on their face, physical appearance or other characteristics that make a person unique. Nowadays, technology allows us to make the exact identification by using Facial Recognition Systems (FRS). A computer does not perceive a face but learns a set of data representing various pixels. Consequently, the human eye is improved and replaced, and now this process can be completed automatically using pattern recognition. In this regard, the European Commission refers to the Artificial Intelligence Act (AIA) as a proposal that promises to establish a general framework with many essential requirements for AI-based systems. Numerous concerns are up in the air, from how to tackle these problems to what courses of action the developers of the systems should take. This research aims to debate the treatment of FRS under the AIA. Consequently, it will analyze the prohibitions of certain Artificial Intelligence practices and the classification of high-risk AI systems that directly impact the use of FRS. Next, the problem of bias will be examined, with specific emphasis on the development stage of an AI system and human oversight is essential to achieve bias mitigation. The implications of using algorithms daily can either open or close opportunities for people. In that sense, it stands to reason to instruct Artificial Intelligence to be intelligent enough, so it does not discriminate against anyone based on gender, race, religion, sex, or any other factor.